UANG DAN MONETER ISLAM DALAM SISTEM MONETER GANDA DI INDONESIA - Muhammad Nurul Alim; Djaka Suryadi (STAI Asy-Syukriyyah, 2021)
The Islamic monetary system in the dual monetary system has not been able to avoid the use of conventional banking instruments, namely the fiat money and fractional reserve banking (FRB) system and only the profit-sharing system that can be applied instead of the interest system. The purpose of this study is to analyze money and the role of the Islamic monetary system in the dual monetary system. This study applies qualitative descriptive analysis by literature study. The results show that Islamic monetary with flow concept and economic value of time can play a role in the dual monetary system in Indonesia by encouraging investment, production and distribution, as well as the application of sharia contracts and the imposition of zakat. The research is expected to be useful for the monetary authorities to activate Islamic financial institutions in order to increase their role in the monetary system in Indonesia.